Germline gene editing and the precautionary principle - Koplin, J; Gyngell, C; Savulescu, J (Wiley, 2019)
The precautionary principle aims to influence decision‐making in contexts where some activity poses uncertain but potentially grave threats. This perfectly describes the controversy surrounding germline gene editing. This article considers whether the precautionary principle should influence how we weigh the risks and benefits of human germline interventions, focusing especially on the possible threats to the health of future generations. We distinguish between several existing forms of the precautionary principle, assess their plausibility and consider their implications for the ethics of germline modification. We also offer a novel form of the precautionary principle: the sufficientarian precautionary principle. Some plausible versions of the precautionary principle recommend placing somewhat greater weight on avoiding threats to future generations than on achieving short‐term benefits. However, no plausible versions of the precautionary principle entail that we should outright reject the use germline gene editing in human reproduction and some, such as the sufficientarian version, might endorse its use.